Gracilis tendon autograft for medial patellofemoral ligament reconstruction in a 47 years old female with recurrent patellar instability: a case report - Koentjorowibowo, Albertus A.; Laksana, Komang M. (International Journal of Research in Medical Sciences, 2023)
The medial patellofemoral ligament (MPFL) is a static soft tissue structure that important to prevent subluxation and dislocation of the lateral patella. Chronic patellar instability and recurrent dislocation of patella may lead to further cartilage injury, limitation of daily living activities, limit return to sport and also can lead to severe patellofemoral arthritis of the knee. MPFL reconstruction has been suggested as a surgical treatment for chronic patellar instability. There are many techniques exist, the most important rules to avoid surgical failure and complications. Nowadays, there is no literature evidence for the best reconstruction technique. Many kind of graft choices and affordability of the implant are also become the defining factors, which trying to simulate the native function of MPFL precisely.